THE CAPITAL PRINCIPLE. - Broad, Samuel J. (The Accounting Review, 1942)
Abstract The author was asked to discuss the section of the Statement of Accounting Principles, which deals with capital and he shall endeavor to confine his remarks to that subject though it may be necessary occasionally to refer to related statements made in other sections. The initial words in the section dealing with capital are: corporate capital, the equity of stockholders of all classes in the enterprise. The author thinks this specification should be kept clearly in mind. What is being discussed in the pamphlet is the accountability of a corporation to its stockholders. It is not the economic capital of the corporation which would be represented by its assets, nor is it the capital from the standpoint of the stockholders. Accounting principle relates primarily to the interpretation of transactions, which have occurred. From the standpoint of ethics it might be argued that it would be unfair to take capital contributed by stockholders of one class and use it to buy shares from another class of stockholders. Rights of different classes of stockholders are established by law and by the contract contained in charter of the corporation.